Effect of 25-hydroxyvitamin D3 on periparturient Yili mare and foal health - Xie, Xinjie; Kamal, Mahmoud; Li, Yonggang; Li, Mingqian; Wang, Jinhe; Hui, Jie; Li, Fengming (Frontiers in Animal Science, 2026)
The periparturient period in mares is metabolically demanding and requires optimal nutrition to support maternal health and fetal development. Vitamin D3, particularly its metabolite 25(OH)D3, plays crucial roles beyond bone health, including immune and antioxidant functions. This study investigated the effects of supplementing pregnant and lactating mares with 25-hydroxyvitamin D3 (25(OH)D3) at a dose of 120,000 IU/day during late gestation and early lactation. Twelve Yili horses were randomly divided into two groups of six, matched by gestation and foaling date. One group received a standard diet, while the other was supplemented with 120,000 IU/day of 25(OH)D3 for 60 days (30 days before and 30 days after birth). Serum and milk samples were collected at the start and midpoint (days 0 and 30) for analysis of 25(OH)D3, mineral concentrations (calcium and phosphorus), proteins, lipids, antioxidants, immunoglobulins, and cytokine levels. The supplementation significantly elevated serum and milk concentrations of 25(OH)D3, calcium, phosphorus, glucose, total protein, and globulin, whereas bilirubin levels diminished in both mares and foals (P < 0.05). In supplemented mares, milk fat percentage, protein content, and immunoglobulin levels (IgA, IgG, and IgM) were elevated (P < 0.05). Improvements were observed in immunoglobulin levels, inflammatory markers, and antioxidant capacity in the supplemented group (P < 0.05). In conclusion, 25(OH)D3 supplementation in pregnant and lactating mares enhanced serum and milk nutrient levels, decreased bilirubin levels, and increased immunoglobulin levels. It also boosted antioxidant capacity and immunoglobulin levels and reduced cytokine levels in both mares and foals.